The misconceptions on MSE research in an emerging market economy: The role of household interference in Indonesia - Ramel Yanuarta RE; Elfindri; Fajri Muharja; Donard Games (Cogent Business & Management, 2023)
This study examines the effect of household interference on business returns and household economic welfare of Micro and Small Enterprises (MSEs). This study employs a quantile regression method involving 7,020 households as the sample. The data are taken from the Indonesian Family Life Survey (IFLS) in two waves (2007 and 2014) to show the returns on microbusinesses. Variables such as unpaid workers, direct consumption of business revenue, and home-based businesses affect profits and household expenditures per capita. This study shows an overlap between MSEs and household business activities in emerging economies. This is contrary to most previous studies on MSEs that have separated businesses and households, thus MSEs' performance could not be properly defined and analyzed. Besides, most Indonesian government policies and efforts only address business activities driven by opportunity, and few accommodate business activities driven by necessity. This research can provide clear evidence to policymakers who tend to adopt a "one size fits all" approach that returns to microbusinesses should be based on household welfare effects as well. This is because microbusinesses provide a livelihood and a means to address economic vulnerabilities, not simply taking advantage of an opportunity.
Keywords: D13; O17; P31; P36; 650; economic welfare; household interference; micro and small enterprises; quantile regression; return; the Indonesian family life survey